Factors associated with postpartum hemorrhage in selected Southern Oromia hospitals, Ethiopia, 2021: an unmatched case-control study - Belda Negesa Beyene; Dube Jara Boneya; Shiferaw Gelchu Adola; Seboka Abebe Sori; Hirut Dinku Jiru; Nurye Sirage; Abdurazak Awol; Girma Tufa Melesse; Zelalem Jabessa Wayessa; Ahmedteyib Jemalo; Abebaw Kebede; Derese Eshetu; et al. (Frontiers Media S.A., 2024)
BackgroundAround one-fourth of maternal deaths worldwide are attributed to hemorrhage. One of the prevalent types of maternal hemorrhage is postpartum hemorrhage. In spite of this, there is very little data on postpartum hemorrhage. Thus, the intention of this study was to determine factors associated with postpartum hemorrhage among mothers who gave birth in the selected Southern Oromia hospitals in Ethiopia.MethodsAn institutional-based, unmatched case-control study was employed on a sample of 333 (83 cases and 250 controls) mothers who gave birth from March 1-30, 2021. Standardized and pretested check-lists were used to retrieve data from patients' cards, delivery registration, and operation registration logbooks. Epi Data Version 3.1 was used to enter data, while SPSS Version 25 was used for analysis. Multi-variable logistic regressions were used to identify the determinants of postpartum haemorrhage with a 95% confidence interval and p-value less than 0.05.ResultsMothers who have no antenatal care follow-up (AOR = 1.94, 95% CI = 1.03, 3.64), had pre-partum anemia (AOR = 5.68, 95% CI = 3.13, 10.32), hypertensive disorder during pregnancy (AOR = 3.3, 95% CI = 1.13, 9.64), intrauterine fetal death (AOR = 4.21, 95% CI = 1.68, 10.58), and genital tract trauma during delivery (AOR = 3.23, 95% CI = 1.52, 6.89) were found as determinants of postpartum haemorrhage.ConclusionThe study showed that factors such as lack of antenatal care, pre-partum anemia, pregnancy-related hypertension, intrauterine fetal death and genital tract trauma during delivery were responsible for postpartum hemorrhage. The early introduction of antenatal care services for all mothers plays a crucial role in reducing postpartum hemorrhage.